Pendampingan Pemahaman Teknologi Siswa Kelas Lima Melalui Aplikasi Google Classroom - Suci Suciati; Nilam Sari Safitri; Arie Pratama Putra; Andi Nur Vira Dela Yandini AM (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Assistance in understanding google classroom is one of the things that is prioritized by elementary school students in the fifth grade. Google Classroom is a free application or web service that can be an option for students to use to help the learning process at school. However, based on observations made at schools, the use of the Google Classroom application is still very rarely implemented in schools. Knowledge from human resources in schools is the main factor in the application of Google Classroom, which is still very minimal, and many stakeholders even think that digital-based learning is still not very important in learning at school. Based on these findings, it is very necessary to carry out assistance in understanding student technology through the Google Classroom application at school. This community service uses a descriptive method. It is hoped that the implementation of mentoring students' understanding of technology through the Google Classroom application can help students to understand how to use the Google Classroom application so that it makes them easier, and helps them in the learning process at school.